Executive Committee Minutes 2010-05-20 - Academic Senate:::::::::
Agenda approved. Correspondence. Statewide Senator Report. Vice President of Administration and Finance Report. Vice President of SAEM Report. Provost Report. Senate questions regarding an online forum resolution amended and approved for Senate agenda. Emeritus Faculty Position on the Senate approved for Senate agenda. BS changes in Geology, Name change of LSEE to LEEE, and Linguistics minor move from Anthropology to English approved for Senate consent calendar. 3-Unit GE Policy approved for Senate agenda. Curriculum Guide changes approved as information item for Senate. Faculty Listserv approved. Senate agenda approved. Faculty Governance Assigned Time proposal amended and approved for forwarding to Provost.